Study on the separation mechanism of icing adhesion and fracture on the surface of 6061 aluminum alloy - Jing Cui; Dezheng Jiang; Zhiwei Xing; Guangfeng Yang (Case Studies in Thermal Engineering)
The phenomena of icing and frost pose a significant threat to aviation safety. Understanding the adhesion mechanisms of surface ice and the fracture and separation mechanisms of ice accretion is fundamental to de-icing operations and the design of surfaces with anti-icing functionalities. While the toughness and fracture mechanisms of ice accretion have been extensively studied, there is a lack of research focusing on the stress- and toughness-driven fracture and separation mechanisms at the ice-substrate interface. This study combines experimental research, numerical simulations, and mechanistic analysis to investigate the interfacial fracture mechanism during the tensile separation of cylindrical ice accretions on aluminum alloy surfaces. Experimental results reveal that surface roughness is directly proportional to adhesion strength, while adhesion strength is inversely proportional to the contact area under the same roughness. A cohesive zone model (CZM) is employed to analyze the micro-scale stress and deformation of ice fracture. By integrating experimental data with numerical simulations, the influence mechanisms of surface roughness and contact area on ice adhesion strength are elucidated.